A. Sativum in the Prevention of Schistosomiasis in Sokoto, Nigeria: Evaluation of Phytochemical Contents, Acute Toxicity, and Effect on Some Kidney Function Parameters in Rats - Abdulkarim, Yalli Abu; Yabo, Asiya Gidado; Dikko, Malami; Sarkingobir, Yusuf; Usman, Mudassiru (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Schistosomiasis is an infectious disease of public health importance in the African countries. Due to poor prevention, poverty, and poor settings; areas like Sokoto, Nigeria are battling with the disease. Consequently, people are compelled to use preventive measures locally. There is recorded use of A. sativum for the prevention of schistosomiasis without enough scientifically supported information in that regards. Therefore, this work evaluated phytochemicals, acute toxicity, and subchronic toxicity (effects on some kidney indices). Standard methods and reagents of analytical grade were utilized. The work reveals the presence of some phytochemicals, no acute toxicity (at 4000 mg/kg body weight), as well as no major change in the urea, uric acid, and creatinine levels. 1.111 mg/dl to 1.118 mg/dl creatinine, 1.011 mg/dl to 1.025 mg/dl urea, and 1.120 mg/dl to 1.140 mg/dl uric acid were determined in control and highest dose (4000 mg/kg body weight) (p<0.05). This indicates that, the plant is likely to elicit little effects on the experimental animals. Much work is important to evaluate sufficiently the safety of the A. sativum in prevention of Schistosomiasis in the Sokoto, Nigeria.